Factors Determine The Survival Of Mustahiq Micro-Entrepreneurs In The National Zakat Board (Baznas) Of West Java Province - Rosalina, Hamdah; Bahri, Efri Syamsul; Kamal, Mustafa (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2023)
This study aims to examine the factors determining mustahiq micro-entrepreneurs’ viability. The method used in this research is quantitative with a descriptive approach. The data was obtained by distributing questionnaires to 90 mustahiq micro-entrepreneurs at the National Amil Zakat Agency (BAZNAS) in West Java Province. Sampling using purposive sampling. Furthermore, data analysis uses descriptive statistics and multiple linear regression analysis. The analytical tool used is IBM SPSS version 23. The results of this study indicate that productive zakat, competence, and intention significantly affect the business continuity of mustahiq. The R-Square value in this study is 0.678, which indicates the influence of productive zakat variables, competencies, and intentions of 67.8%, while 32.2% is influenced by other variables outside the variables studied. These findings provide recommendations to zakat management entities and policymakers so that the resources provided to mustahiq are given more optimally in order to be able to contribute to business continuity and the success of mustahiq micro-entrepreneurs.